Determination of serum anti-Mullerian hormone levels in a low-prognosis women treated in-vitro fertilization/intracytoplasmic sperm injection: A cohort study - Ferdy Royland Marpaung; Amang Surya Priyanto; Fitri Ayu Kusumawati; Sidarti Soehita; Aryati (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Outcome prediction of participants treated with in-vitro fertilization or intracytoplasmic sperm injection (IVF/ICSI) using anti-Mullerian hormone (AMH) concentration has been widely used. According to the patient-oriented strategies encompassing individualized oocyte number (POSEIDON) definition, low prognosis Bologna responders have changed from poor. This definition divides low prognosis into 4 groups. Objective: The purpose of this study was to assess blood AMH levels in the group of women treated with IVF/ICSI who were thought to have a low prognosis. Materials and Methods: A retrospective cohort study among 252 suspected low-prognosis group participants was assessed between January 2016 and December 2019 at Morula IVF, National hospital, Surabaya, Indonesia. Observed AMH serum levels and pregnancy rates were compared among 4 subgroups. Results: The AMH cutoff value was 1.7 ng/mL with a sensitivity of 86.7% and a specificity of 70% for diagnosing low-prognosis women using POSEIDON criteria. There was no difference in the pregnancy rate between those groups (p > 0.05). Conclusion: AMH levels may indicate a poor prognosis for women having IVF/ICSI in accordance with POSEIDON guidelines. To predict the poor prognosis in women, the cutoff value must be identified.